2013
DOI: 10.1007/s00330-013-2819-9
|View full text |Cite
|
Sign up to set email alerts
|

How to differentiate benign from malignant myometrial tumours using MR imaging

Abstract: • MRI is widely used to differentiate benign from malignant myometrial tumours. • By combining T2-weighted, b 1,000 and ADC features, MRI is 92.4 % accurate. • DWI may limit misdiagnoses of uterine sarcoma as benign leiomyoma. • Patient age is important when considering a solitary myometrial tumour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(86 citation statements)
references
References 15 publications
5
78
2
1
Order By: Relevance
“…However, recent studies suggest that MRI through diffusion and post-contrastographic sequences, represent emerging valuable technique for the differential diagnosis between degenerate leiomyoma and sarcomas [21,22,[25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies suggest that MRI through diffusion and post-contrastographic sequences, represent emerging valuable technique for the differential diagnosis between degenerate leiomyoma and sarcomas [21,22,[25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
“…The same appearance is shown by cellular leiomyomas and some types of degenerated leiomyomas, which then may mime sarcomas. Therefore, the differential diagnosis between myoma and sarcoma can be difficult if it is just based on conventional sequences without administration of contrast agent [19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…Namimoto et al (9) showed that overlap in ADC values between leiomyosarcomas and ordinary leiomyomas (attributed to the "T2 blackout effect," i.e., hypointensity on DWI caused by hypointensity on T2-weighted images) could be resolved with the evaluation of tumor-myometrium contrast ratio on T2-weighted images. Thomassin-Naggara et al (12) reported that by combining the analysis of T2 signal intensity, b1000 images and ADC map, MRI achieved 92.4% accuracy in distinguishing benign and uncertain or malignant myometrial tumors. Therefore, they concluded that DWI may limit misdiagnosis of uterine sarcomas as benign leiomyomas, and should be the first criterion to help radiologists characterize a unique uterine tumor.…”
Section: Mri Featuresmentioning
confidence: 99%
“…Thomassin-Naggara et al [32] in a retrospective study proposed a recursive partitioning model, using b 1000 signal intensity, T2 signal intensity, mean ADC, and patient age which correctly classified benign and malignant lesions in 92.4 % of cases. Adenosarcomas are usually low grade tumours and typically present as polyps.…”
Section: Uterine Sarcomasmentioning
confidence: 99%
“…They have been shown to have low ADC values in the limited studies available [33,34] . Overall studies trying to differentiate leiomyoma from sarcomas in terms of ADC values alone have been inconsistent with considerable overlap in values, ADC could be used as a adjuvant tool along with other parameters to increase the diagnostic confidence to characterize benign from malignant lesions [31][32][33][34][35][36][37] .…”
Section: Uterine Sarcomasmentioning
confidence: 99%